THE IMPORTANCE PERFORMANCE ANALYSIS OF PHYSICAL ENVIRONMENT FROM CUSTOMER PERSPECTIVE AT MCDONALD’S MANADO - Warouw, Raymond; Lapian, Joyce (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
McDonald’s Manado is one of fast food restaurants that improved their service, it can be seen from their physical environment. The aim of this research is to analyze the importance and performance of physical environment at McDonald’s Manado, whether the use of physical environment of McDonald’s is optimal or not. The type of this research is descriptive quantitative methods by using Importance-Performance Analysis (IPA) as the analytical tool. The population of this research is the customers of McDonald’s Manado where the sample size is taken from 100 customers. This research findings that Walkways Arranged is important but not good in the performance for customers. Style of Décor, Parking Space, Lighting, Menu Information are important and have a good performance to customers. Noise, Scent, Signage, Temperature, Shape of Furnishing have low priority to customers. McDonald’s management should give special attention in order to improve and  increase the performance of Walkways Arranged. The management should keep give the highest attention to Style of Décor, Parking Space, Lighting, Menu Information in order to keep the highest performance that have been achieved. Noise, Scent, Signage, Temperature, Shape of furnishing have low priority, so the management should not give more attention to this attributes. Keywords: physical environment, importance-performance analysis, mcdonald’s